Congenital heart disease and chromossomopathies detected by the karyotype - Patrícia Trevisan; Rafael Fabiano M. Rosa; Dayane Bohn Koshiyama; Tatiana Diehl Zen; Giorgio Adriano Paskulin; Paulo Ricardo G. Zen (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To review the relationship between congenital heart defects and chromosomal abnormalities detected by the karyotype.DATA SOURCES: Scientific articles were searched in MEDLINE database, using the descriptors "karyotype" OR "chromosomal" OR "chromosome" AND "heart defects, congenital". The research was limited to articles published in English from 1980 on.DATA SYNTHESIS: Congenital heart disease is characterized by an etiologically heterogeneous and not well understood group of lesions. Several researchers have evaluated the presence of chromosomal abnormalities detected by the karyotype in patients with congenital heart disease. However, most of the articles were retrospective studies developed in Europe and only some of the studied patients had a karyotype exam. In this review, only one study was conducted in Latin America, in Brazil. It is known that chromosomal abnormalities are frequent, being present in about one in every ten patients with congenital heart disease. Among the karyotype alterations in these patients, the most important is the trisomy 21 (Down syndrome). These patients often have associated extra-cardiac malformations, with a higher risk of morbidity and mortality, which makes heart surgery even more risky.CONCLUSIONS: Despite all the progress made in recent decades in the field of cytogenetic, the karyotype remains an essential tool in order to evaluate patients with congenital heart disease. The detailed dysmorphological physical examination is of great importance to indicate the need of a karyotype.